The personal struggles of 'national' educators working in 'international' schools: an intercultural perspective. (20th October 2017) - Savva, Maria
ABSTRACT: This paper looks at how personal struggles associated with the overseas setting caused changes in the intercultural perspective of 30 Anglophone educators working in international schools. Situated within a social constructivist framework, interview methods were utilised to build a collective narrative shared by educators. Findings reveal that although prolonged exposure to new cultural norms elicited changes in intercultural perspective, these changes were not related to traditional notions of cultural immersion but – rather paradoxically – to educators' inability to integrate into the host cultures. Obstacles educators faced while abroad included a lack of language proficiency, living in countries that were sometimes antithetical to Western ideals and discriminatory practices based on national and/or race affiliation.